9.8k views
20 votes
How do I solve this and get y?

How do I solve this and get y?-example-1
User Yugal
by
6.4k points

1 Answer

9 votes

Answer:

y = (1 -3x)/x

Explanation:

Rearrange terms to get an expression that has y as a multiplier, and divide by the coefficient of y.


(1+2xy)/(y+1)=3x\qquad\text{given}\\\\1+2xy=3x(y+1)\qquad\text{multiply by $(y+1)$}\\\\1+2xy=3xy+3x\qquad\text{eliminate parentheses}\\\\1-3x=xy\qquad\text{subtract $(3x+2xy)$}\\\\\boxed{y=(1-3x)/(x)}\qquad\text{divide by the coefficient of y}